Multifrequency and Multistatic Inverse Synthetic Aperture Radar, with Application to FM Passive Radar. (9th December 2009) - Ginolhac Ginolhac, Guillaume Guillaume; Schmitt Schmitt, Françoise Françoise; Daout Daout, Franck Franck; Forster Forster, Philippe Philippe
Abstract : This paper deals with the imaging of a moving target using a multifrequency and multistatic radar consisting in one receiver and several narrowband transmitters. Considering two hypotheses about the studied target, we derive two multistatic inverse synthetic aperture radar processors: the first one, which models the target as a set of isotropic points, performs a coherent sum of bistatic images; the second one, which models the target as a set of nonisotropic points, performs an incoherent sum of bistatic images. Numerical simulations are done, which demonstrate the efficiency of the second processor. We also apply both processors to a multistatic passive radar scenario for which the transmitters are FM stations located in a realistic configuration. We study the system performance in terms of resolution and sidelobe levels as a function of the number of transmitters and of the integration time. Both processors are applied to similar complex targets for which the scattered fields are simulated by a numerical electromagnetic code. The resulting multistatic radar images show interesting characteristics that might be used by classification algorithms in future work.